Design and manufacturing of 3D high-precision micro-fibrous poly (l-lactic acid) scaffold using melt electrowriting technique for bone tissue engineering. (15th November 2021) - Meng, Jie; Boschetto, Francesco; Yagi, Shinichi; Marin, Elia; Adachi, Tetsuya; Chen, Xuefei; Pezzotti, Giuseppe; Sakurai, Shinichi; Yamane, Hideki; Xu, Huaizhong
Graphical abstract: High precision micro fibrous Poly (l -lactic acid) scaffold made via self-assembled electrohydrodynamics guided melt electrowritten (MEW) approach and it plays a crucial role for bone tissue engineering. Highlights: Poly (l -lactic acid) PLLA scaffold was firstly made by melt electrowriting (MEW). The electrohydrodynamics of the PLLA molten jet was systematically studied. PLLA scaffolds with adjustable filament diameter and pore size were fabricated. The MEW PLLA scaffold exhibits in vitro potential for bone tissue engineering. Abstract: The thermally sensitive polymer, poly (l -lactic acid) PLLA, is first printed to a high-resolution object using an advanced 3D printing technology, called melt electrowriting (MEW). The MEW processing conditions are systematically investigated to manufacture PLLA scaffolds with adjustable filament diameter and pore size for the application of bone tissue engineering. To this end, the relationships among the rheological behavior of the molten polymer, the electro-hydrodynamics of the jet, and the processing parameters (applied voltage, collection speed, and flow rate) are illuminated. The scaffold with relatively high deposition accuracy and crystallinity of PLLA is achieved when the printing speed was set slightly above the critical translation speed. The MEW PLLA scaffold with filament diameter of 40 μm and pore size of 200 μm is evaluated with KUSA-A1 cells to prove its in vitro potential. This is a milestone work for MEW since it supplies one of the best strategies to design and manufacture an essential biobased polymer for tissue engineering.